2013
DOI: 10.1063/1.4807604
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur 1s near edge x-ray absorption fine structure spectroscopy of thiophenic and aromatic thioether compounds

Abstract: Thiophenic compounds are major constituents of fossil fuels and pose problems for fuel refinement. The quantification and speciation of these compounds is of great interest in different areas such as biology, fossil fuels studies, geology, and archaeology. Sulfur 1s Near-Edge X-ray Absorption Fine Structure (NEXAFS) spectroscopy has emerged as a qualitative and quantitative method for sulfur speciation. A firm understanding of the sulfur 1s NEXAFS spectra of organosulfur species is required for these analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 78 publications
4
12
0
Order By: Relevance
“…Behyan et al attribute the two main features of the spectrum to be 1s → σ*(SC)/π*(CC) transitions. The spectrum reported by Behyan et al 36 for neat liquid diphenyl sulfide is similar to that of diphenyl sulfide in toluene solution reported here (Figure 1), setting aside distortion due to fluorescence self-absorption, and differences in energy calibration. Behyan et al discuss the possibility that different conformers might contribute to the liquid spectra, 36 and in particular an all-planar conformation with phenyl and sulfur colocated in one plane.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Behyan et al attribute the two main features of the spectrum to be 1s → σ*(SC)/π*(CC) transitions. The spectrum reported by Behyan et al 36 for neat liquid diphenyl sulfide is similar to that of diphenyl sulfide in toluene solution reported here (Figure 1), setting aside distortion due to fluorescence self-absorption, and differences in energy calibration. Behyan et al discuss the possibility that different conformers might contribute to the liquid spectra, 36 and in particular an all-planar conformation with phenyl and sulfur colocated in one plane.…”
Section: Resultssupporting
confidence: 86%
“…As noted above, we predict that the vapor-phase and solution XAS of diphenyl sulfide ought to be very similar. This is in contrast to previous reports of a remarkably different spectrum for vapor-phase diphenyl sulfide, with the main absorption shifted to lower energy by ∼0.4 eV and lacking a pronounced high-energy peak . We therefore measured the vapor-phase spectrum of diphenyl sulfide, a comparison of which with the liquid-phase toluene solution spectrum is shown in Figure .…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies of thiophene near-edge spectra 40,43,44 reported intense features at the edge corresponding to low-lying transitions that have been assigned as 1s → (S–C)π* and 1s → (S–C)σ*, with the former at slightly lower X-ray energy. In order to confirm these assignments we first studied single crystal polarized spectra of thiophene-3-carboxylic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] The specificity of NEXAFS spectroscopy renders it an attractive technique for investigating elements that are essentially silent by NMR spectroscopy, for example, sulfur. [26][27][28][29] NEXAFS spectroscopy involves the study of the absorption of an X-ray photon by the element of interest, leading to promotion of an electron from a core orbital to a previously unoccupied molecular orbital (UMO). Absorption is generally indirectly monitored by measurement of either the fluorescence yield (FY) or the electron yield (EY), e.g.…”
Section: Introductionmentioning
confidence: 99%